The role of social support networks in proxy Internet use from the intergenerational solidarity perspective. Issue 2 (May 2018) - Dolničar, Vesna; Grošelj, Darja; Filipovič Hrast, Maša; Vehovar, Vasja; Petrovčič, Andraž
Highlights: Relationship between social support networks and proxy Internet use is examined. Ego-centered social network data from a nation-wide representative sample are used. The size of the social support networks is not associated with proxy Internet use. (Grand-)children in socializing networks increase the odds of proxy Internet use. Socio-demographic characteristics have an important role in proxy Internet use. Abstract: Digital inequalities research has documented a set of practices related to people's Internet use that questions the binary division between Internet users and non-users. In particular, among older adults, a considerably large group of individuals has been identified as not using the Internet by themselves; rather, they ask members of their personal networks to do things online for them—they "use" the Internet by proxy. Since previous research shows that children and grandchildren are important sources of help when it comes to Internet use, the current paper indicates that the notion of intergenerational solidarity is a sound conceptual basis for understanding the relationship between social support networks and proxy Internet use among Internet non-users. Notably, the concept of functional solidarity as a dimension of intergenerational solidarity is advanced, as this relates to the frequency of the intergenerational exchange of resources and services encompassing various types of assistance and support offered between two generations. Empirically, this paper investigates how the two types of social support networks and their characteristics are associated with proxy Internet use. The results from multivariate analyses of survey data from a nation-wide representative sample show that when comparing emotional support and socializing networks, only the latter is associated with proxy Internet use: Internet non-users who have (grand-)children in their socializing support network are more likely to engage in proxy Internet use. The results also indicate that non-users who are younger, more educated, have children, and live in urban areas are more inclined to engage in proxy Internet use, regardless of the type of social support. The findings indicate the importance of empirical investigation related to different aspects of functional solidarity, as the effects on proxy Internet use depend on the type of social support.